2017
DOI: 10.1016/j.psyneuen.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Examining habituation and sensitization across repetitive laboratory stress inductions using the MAST

Abstract: Reliably eliciting acute stress repeatedly over time is of indispensable value for research into stress vulnerability and for developing interventions aimed at increasing stress resiliency. Here, we evaluated whether the Maastricht Acute Stress Test (MAST), a potent stress protocol that combines physical and psychosocial stress components, can be used to reliably elicit subjective and neuroendocrine stress responses multiple times. Sixty healthy undergraduate participants were exposed to the MAST on three occa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…the social stress component). Previous studies have shown that the MAST is an effective stress task (Smeets et al., ; Meyer et al., ; Quaedflieg et al., ; Shilton et al., ). The control version included immersion of the left hand into lukewarm water (36 °C), a simple counting task, no video‐taping and no monitoring by the experimenter.…”
Section: Methodsmentioning
confidence: 98%
“…the social stress component). Previous studies have shown that the MAST is an effective stress task (Smeets et al., ; Meyer et al., ; Quaedflieg et al., ; Shilton et al., ). The control version included immersion of the left hand into lukewarm water (36 °C), a simple counting task, no video‐taping and no monitoring by the experimenter.…”
Section: Methodsmentioning
confidence: 98%
“…At all times, participants were allowed to remove their hand from the water and/or stop the entire stress induction procedure (12 participants stopped the procedure, but continued with the ensuing tasks; these participants were included in all data analyses). 82% of our participants showed a cortisol increase of at least 1.5 nmol/l in response to the stress induction (Miller et al, 2013), which falls in the normal range of responding (Quaedflieg et al, 2016). After the stress induction, participants were allowed to put their hand into lukewarm water for approximately 1 min to warm up their hand, which also served to prevent additional hand movements during the following task.…”
Section: Stress Induction and Measurementsmentioning
confidence: 97%
“…Acute stress was elicited using the 'Maastricht Acute Stress Test' (MAST), a potent and reliable procedure to elicit subjective, autonomic and glucocorticoid stress responses (Quaedflieg et al, 2017;Smeets et al, 2012). To assess the intentional control of fear imaginings, the current study employed an adapted version of the 'Imagine/No-Imagine' task, tailored to the retrieval versus suppression of future feared events (Benoit et al, 2016…”
Section: Preprint: Stress Impairs Intentional Forgetting Of Future Fementioning
confidence: 99%